After Arguedas: Historiography and the problem of "the Andean novel" - Rowe, William (1996)
I propose an assemblage of texts —a provocative confrontation of some texts— rather than a commentary. That is why everything that would correspond to a description has been limited as far as possible. The analysis offered is largely in the juxtapositions themselves. First, however, one would have to begin with a preamble to place the materials. Moving from merely Creole historiography to what could be a total image of Peru (recognizable by all) has been one of the concerns of twentieth-century Peruvian historians.